Gene Replacement and Fluorescent Labeling to Study the Functional Role of Exopolysaccharides in Bifidobacterium animalis subsp. lactis - Castro-Bravo, Nuria; Hidalgo-Cantabrana, Claudio; Rodriguez-Carvajal, Miguel A.; Ruas-Madiedo, Patricia; Margolles, Abelardo (Frontiers in Microbiology, 2017)
An extracellular layer of exopolysaccharides (EPS) covers the surface of some Bifidobacterium animalis subsp. lactis strains, which could be of relevance for its probiotic performance. In order to understand the functional characteristics of B. animalis subsp. lactis, two isogenic strains that differ in their EPS-producing phenotype, due to a single mutation in the gene Balat_1410, were studied. By means of a double crossover recombination strategy, successfully used for the first time in bifidobacteria, Balat_1410 in the type strain B. animalis subsp. lactis DSM10140 was replaced by a mutated gene containing a nonsynonymous mutation previously associated with the appearance of a mucoid-ropy phenotype. NMR and SEC-MALS analyses showed that the novel strain harboring the mutation acquired a ropy phenotype, due to the production of a high molecular weight (HMW)-EPS that is not produced in the wild-type strain. Fluorescence labeling of both strains with two fluorescent proteins, m-Cherry and Green Fluorescent Protein (GFP), was achieved by expressing the corresponding genes under the control of using a native selected promoter (the elongation factor Tu promoter). Remarkably, qualitative and quantitative fluorescence analyses demonstrated that the ropy strain displays a lower capability to adhere to human intestinal epithelial cells. In addition, the presence of the HMW-EPS reduced the capability of the producing strain to form biofilms upon three different abiotic surfaces. This work also highlights the fact that different EPS confer variable functional characteristics to the bifidobacterial surface, which may be relevant for the performance of B. animalis subsp. lactis as a probiotic. The construction of molecular tools allowing the functional characterization of surface structures in next generation probiotics is still a challenging issue that deserves further attention, given the relevant role that such molecules must play in the interaction with the host.